The Item versus the Object in Memory: On the Implausibility of Overwriting As a Mechanism for Forgetting in Short-Term Memory - Beaman, C. Philip; Jones, Dylan M. (Frontiers in Psychology, 2016)
The nature of forgetting in short-term memory remains a disputed topic, with much debate focussed upon whether decay plays a fundamental role (Berman et al., 2009; Altmann and Schunn, 2012; Barrouillet et al., 2012; Neath and Brown, 2012; Oberauer and Lewandowsky, 2013; Ricker et al., 2014) but much less focus on other plausible mechanisms. One such mechanism of long-standing in auditory memory is overwriting (e.g., Crowder and Morton, 1969) in which some aspects of a representation are “overwritten” and rendered inaccessible by the subsequent presentation of a further item. Here, we review the evidence for different forms of overwriting (at the feature and item levels) and examine the plausibility of this mechanism both as a form of auditory memory and when viewed in the context of a larger hearing, speech and language understanding system.